Adaptive Block Size and Block Timeout for Hyperledger Fabric Networks - Moura, Ericksulino Manoel de A.; Abreu, Ramon Vítor C. de; Silva, Franciso Airton; Castelo Branco, André Soares; Freitas, Allan Edgard Silva; Gonçalves, Glauber Dias (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
Permissioned blockchains must sustain stable performance under time-varying transaction arrival rates. In Hyperledger Fabric (HLF), block configuration parameters, such as block size (BS) and block timeout (BT), strongly affect performance, particularly throughput and transaction latency. We propose an adaptive framework that monitors network workload and automatically reconfigures BT and BS across consecutive time windows to improve HLF performance. As a proof of concept, we implement two adaptation strategies from the literature within the framework: aHLF (adapted from a batch control for the Practical Byzantine Fault Tolerance protocol) and FabMAN (originally designed for HLF). We then compare the performance of these strategies with the default fixed-block configuration in HLF, based on experiments on an AWS-based HLF network deployment under a dynamic workload profile. Results show that the adaptive strategies outperform the default configuration. In particular, at the peak workload, the best-performing strategy (FabMAN) achieves 44% higher throughput and 38% lower latency than the default configuration, indicating the benefits of the proposed adaptive blockchain framework.